ANALYSIS OF THE BENEFITS OF GREEN BUILDING IN SOUTH AFRICA - Eric Kwame SIMPEH; John SMALLWOOD (Journal of Construction Project Management and Innovation)
This paper investigates the perceptions of built environment professionals with respect to the benefits of green buildings and identifies the benefits regarded as the most important to promote the adoption of green building. The primary data was collected from 106 green building-accredited professionals in both the public and private sectors who are registered with the Green Building Council of South Africa (GBCSA). Response data was subjected to descriptive and inferential statistics, namely factor analysis (FA), ANOVA test, and the paired sample test. The benefits of green buildings emanating from the findings were categorised as socio-economic, financial, and health and community benefits. The paired sample test indicated a statistically significant difference between paired samples: financial benefits, health and community benefits, and socio-economic benefits. However, the test revealed no statistically significant difference between financial benefits and socio-economic benefits. There was no statistically significant difference with respect to the perceptions of respondents concerning financial benefits and health and community benefits. It is important to note that the benefits identified in this research may be limited to the time of the research, since the opinions of people relative to green building consciousness and conditions may change over time. It is anticipated that the most significant benefits identified by built environment stakeholders will create an enabling environment to enhance the adoption of green building. Therefore the findings emanating from this study can be used as a support tool for identifying the most significant benefits that enhance the decision of stakeholders to adopt green building and to provide continuous improvement that is essential for green building to gain competitive advantage over the traditional construction methods.